Foliar application of chelated sugar alcohol calcium fertilizer for regulating the growth and quality of wine grapes - Ma, Tinghui; Hui, Yueran; Zhang, Li; Su, Baofeng; Wang, Rui (International Journal of Agricultural and Biological Engineering, 2022)
The eastern foothills of Helan Mountain are a production area of high-quality wine grapes, but the low content of water-soluble calcium in the alkaline soil in this area has become an important limiting factor for the production of high-end wines. In this study, 7-year-old Cabernet Sauvignon grapes grown at Lilan Winery, which is located at the eastern foot of Helan Mountain in Ningxia, China, were used to examine the effect of exogenous calcium supplementation on fruit growth and berry quality. Calcium sugar alcohol was applied as a foliar spray at 1.2 L/hm2 (T1), 2.4 L/hm2 (T2), 3.6 L/hm2 (T3), 4.8 L/hm2 (T4), and 6.0 L/hm2 (T5) concentrations at the fruit expansion stage, the early stage of grape veraison, the middle stage of grape veraison, and the later stage of grape veraison. Water control was used for comparison. The results showed that foliar calcium supplementation can significantly enhance the photosynthetic characteristics of wine grape leaves, increase the chlorophyll content of leaves, and improve the quality of grape berries. Under the T3 (3.6 L/hm2) concentration of exogenous calcium, the transverse diameter, the longitudinal diameter, and fruit shape index of grapes were the highest, which were increased by 1.71%, 5.33%, and 3.92% compared to the control, respectively. The application of high calcium concentrations (T4 and T5) inhibited the physiological development of grapes. The spike length, hundred-grain weight, yield of wine grapes, sugar-acid ratio, tannin, and total phenols were the highest in the T2 (2.4 L/hm2) treatment. The results of principal component analysis based on multiple indicators showed that foliar application of 2.4-3.6 L/hm2 chelated sugar alcohol calcium on the leaf surfaces of grape leaves was the most suitable for improving the physiological characteristics and berry quality of wine grapes. Keywords: wine grapes, chelated sugar alcohol calcium, mineral elements, berry quality, Helan Mountain DOI: 10.25165/j.ijabe.20221503.5405 Citation: Ma T H, Hui Y R, Zhang L, Su B F, Wang R. Foliar application of chelated sugar alcohol calcium fertilizer for regulating the growth and quality of wine grapes. Int J Agric & Biol Eng, 2022; 15(3): 153–158.